FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT ADOPSI GAS BUMI RUMAH TANGGA DI KECAMATAN LIMAPULUH KOTA PEKANBARU - Putra, Yogi Pratama; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted in Limapuluh district of Pekanbaru city with problems that is (1) What are the factors that affect the rate of adoption of household gas in Limapuluh district of Pekanbaru city? (2) How is the rate of adoption of household gas in Limapuluh district of Pekanbaru city?. The purpose of this study was conducted to determine the factors that influence the adoption of household gas innovation and socio-economic community towards the existence of new innovations in the form of household gas fuel in Limapuluh district of Pekanbaru city. This research is a descriptive quantitative research. The population in this study is the community that installed the household gas in Limapuluh district of Pekanbaru city. With a total sample of 44 respondents and using cross tabulation to test the indicators affecting the adoption of household gas. In the data collection of research using observation techniques and questionnaires. The result of this study indicate that the factors that affect the rate of adoption of household gas that includes the nature of innovation adn socio-economic community by using cross tabulation. Factor of nature of innovation toward adoption of natural gas have positive relationship and very influence of good innovation character then adoption of innovation in society hence will follow good, but socio-economic factor to household gas adoption show less influence because not always having socio-economic status high then it would be good also in adopting new innovation, it is evident in tabulation table cross. While the rate curve adoption of household gas in Limapuluh district there is no visible innovator and pioneer group.The keyword : Nature of innovation, Socio-economic, Level of adoption of household gas